Quantum Mechanics in Hilbert Space - Eduard Prugovecki (New York Dover Publications Inc., 1981)
School of Mathematics and Natural Sciences
MIR No: 165
Order Date: 2024-07-08
Order No: CU/OPEX/LIBRARY/24/2024-25
Received Date: 2024-09-20
Keywords: Hilbert Space, Quantum Theory